Application of correlations and principal component analysis in the study of quantitative traits of a reduced population of avian genotypes from Paraguay - Martínez-López, Roberto (2024)
In animal characterization research it is essential to establish ranges of typical and fluctuating behaviours of its variables and parameters. For this, the use of robust statistical inferences constitutes a relevant tool. Thus, the study of body traits in a rustic dual-purpose avian population was approached, through correlation and principal component analysis (PCA), contributing to its morphometric characterization and verifying the usefulness of the statistical methods used in a small group. In total, 52 chickens (males and females) were evaluated, classified as adults and older adults, analysing a series of quantitative traits. An association was found between live weight and skull width, middle finger length, wing length (p < 0.01), back length, keel length, breast width, beak length and tarsus length (p<0.05), in adult males, while for older birds calculations are suggested as selection criteria between live weight with keel length and neck length. On the other hand, in adult females, live weight did not show the zootechnical relevance observed in males, while in older females a positive relationship of some body characteristics with live weight was evident. The correlation analysis was useful to provide morphometric links in both sexes and age groups, but not the PCA, which showed good performance in body measurements of males before that of females, in conditions of reduced effective population size (risk) and with native phenotypes.